Cytospin preparation from residual material in needle hub: Does it add to fine needle aspiration diagnosis? - Gupta, Shilpa; Deka, Lopamudra; Gupta, Ruchika; Gupta, Kusum; Kaur, Charanjeet; Singh, Sompal (Annals of Pathology and Laboratory Medicine, 2015)
Background: Fine needle aspiration is currently the most favored technique for pre-operative diagnosis of most palpable and certain non-palpable masses. The present study aimed at exploring the utility of cytospin preparation from residual material in the needle hub for assisting in routine cytologic diagnosis. Methods: For this prospective study, 100 cases of fine needle aspiration from lymph node, breast, soft tissue, thyroid and salivary glands were included. After preparation of routine smears, material in needle hub was rinsed in saline and cytospin preparation was made. Routine and cytospin preparations were assessed for cytologic diagnosis and results compared. Results: Of the 100 cases included, the cytospin preparation showed good staining in all (100%). Cellularity was adequate in 90% of the cases with satisfactory cellular preservation in 72% cases. In 16 cases (16%), the diagnostic material was present in cytospin preparation while routine smears were inadequate for opinion. Â Conclusion: Cyto-centrifugation of the residual material in needle hub after fine needle aspiration improves the diagnostic yield of routine smears. Hence, this technique can be utilized to reduce the number of re-aspirations, especially at centers where the requisite equipment is already available.